(untitled) (International journal of artificial intelligence, 2024)
Artificial Intelligence( AI) is increasingly integrated into aspects of human life, including health care, with its applications reaching robotic surgery, virtual nursing assistants, image analysis etc. In the light of transformation potential of AI, the World Medical Association has also supported the fact that education related AI training is essential and should be included in the curriculum of all medical degrees in the near future.Hence, the current study was designed to assess perceptions among medical students related to AI in medicine, their perceived needs with respect to structured AI training during medical education and the understanding of ethical dimensions arising from AI in healthcare.